Az nuskhahā-yi Istānbūl Dastnivīshā-ī dar falsafah, kalām, ʿirfān - Ḥāiʿrī, Sayyid Muḥammad ʿImādī (Persian E-Books Miras Maktoob, 2019)
For those working with Islamic manuscripts the libraries of Istanbul have always been a treasure-trove. New discoveries are frequently reported and of many texts, the oldest or only copy is kept in some library in Istanbul. Since the publication of the defters of the Istanbul libraries in the late nineteenth and early twentieth century, many more catalogues and handlists have been produced in an effort to render the immense amount of material more accessible. Even if the bulk of this work is done by Turkish specialists, foreign scholars, too, do their part. The present collection of research notes is a case in point. They describe a number of important Arabic and Persian manuscripts in philosophy, theology and mysticism selected for publication by the Written Heritage Research Centre in Tehran. Some of these manuscripts are in the hand of, or contain marginalia by, Naṣīr al-Dīn Ṭūsī (d. 672/1274), Najm al-Dīn Kātibī (d. 675/1276), and others